Legalitas Perjanjian Kerja Sama Luar Negeri Pemerintah Daerah Di Masa Pandemi Covid-19 - Efie Baadilla; Dyah Ridhul Airin Daties (SASI, 2021)
The aims of this study is to analyze the legality of regional foreign cooperation agreements during the COVID-19 pandemic. This research is a normative juridical study, with the type of library research. In order to support this research process, the approach used is a statute approach and a conceptual approach. The results show that the legality of the regional government foreign cooperation agreement is related to the status of the regional government which is an extension of the central government through regional autonomy given the authority to carry out international cooperation through an agreement. This authority must be exercised by taking into account the potential of natural resources and the needs of the community, especially during the COVID 19 pandemic.